Optimization of diagnostic strategy for non-invasive cell-free foetal RHD determination from maternal plasma - Pazourkova, Eva; Zednikova, Iveta; Korabecna, Marie; Kralova, Jana; Pisacka, Martin; Novotna, Michaela; Calda, Pavel; Horinek, Ales (Vox sanguinis, 2021)
BACKGROUND AND OBJECTIVES: The aim of the study was to optimize routine non-invasive prenatal detection of fetal RHD gene from plasma of RhD-negative pregnant women (the median of gestational age was 25 weeks, range 10-38) to detect RhD materno-fetal incompatibility and to avoid the redundant immunoprophylaxis. MATERIALS AND METHODS: Initially only one exon of RHD gene (exon 10) was investigated in 281 plasma samples (144 verified after delivery), in the second phase three RHD exons (5, 7, 10) were analyzed in 246 samples of plasma and maternal genomic DNA (204 verified) by real-time PCR method. Detection of Y-chromosomal sequence DYS-14 and five X-chromosomal insertion/deletion polymorphisms was used to confirm the fetal cfDNA detectability in plasma. Specific polymorphisms in RHD gene were detected by sequence-specific primer PCR in nine samples. RESULTS: When only the RHD exon 10 was tested, 2·8% of verified samples were false positive and 3·5% false negative. With three RHD exons (5, 7, 10) and maternal genomic DNA testing, only one case was false negative (0·5%). Nine samples were inconclusive due to RHD-positive results in maternal genomic DNA. These samples were analyzed for specific mutations in RHD gene. Combination of both methods for fetal cfDNA verification succeeded in 75% of tested group. CONCLUSION: Implementation of analysis of three RHD exons and maternal genomic DNA to routine practice lowers dramatically the ratio of false positive and negative results. This method enables more accurate determination of fetal RHD status with the reduction of unnecessary medical care and RhD immunoprophylaxis.
Keywords: Rh-Hr Blood-Group System; kvantitativní polymerázová řetězová reakce; prenatální diagnóza; Genotype; Infant; Pregnancy; těhotenství; Fetus; Prenatal Diagnosis; Real-Time Polymerase Chain Reaction; krevní skupiny - systém Rh-Hr; plod; lidé; ženské pohlaví; Humans; kojenec; DNA; genotyp; Female